PENGGUNAAAN MODEL KOOPERATIF TIPE TGT DENGAN MULTIMEDIA DALAM PEMBELAJARAN IPA SISWA KELAS V SDN 6 PANJER TAHUN AJARAN 2014/2015 - Megasusilowati, Erin (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract : The Use of Cooperative Models TGT with Multimedia in Natural Science Learning at Fifth Grade Students of Panjer 6 Elementary School Year 2014/2015. This study aims to improve science learning process. The subject of research were 34 students of fifth grade Panjer 6 Elementary School. Classroom Action Research was conducted in three cycles. Every cycle there are two meetings that consist of planning, action, observation, and reflection. Data collection techniques were test, observation and interviews. The validity data using triangulation of data source and technique. The data comes from students, colleagues, fifth grade teacher, analyst and document. The results showed the use of cooperative models TGT with multimedia can increase natural science learning for fifth grade student of elementary school. Keywords: TGT, Multimedia, Natural Sciences Learning Abstrak : Penggunaaan Model Kooperatif Tipe TGT dengan Multimedia dalam Pembelajaran IPA Siswa Kelas V SDN 6 Panjer Tahun Ajaran 2014/2015. Penelitian ini bertujuan meningkatkan pembelajaran IPA siswa kelas V. Subjek penelitian ini adalah siswa kelas V SDN 6 Panjer sejumlah 34 siswa. Penelitian Tindakan Kelas ini dilaksanakan dalam tiga siklus. Setiap siklus terdapat dua pertemuan yang terdiri atas tahap perencanaan, pelaksanaan, pengamatan, dan refleksi. Teknik pengumpulan data dengan tes, observasi dan wawancara. Validitas data menggunakan triangulasi sumber data dan teknik. Data berasal dari siswa, teman sejawat, guru kelas V, peneliti, dan dokumen. Hasil penelitian menunjukkan penggunaan model kooperatif tipe TGT dengan multimedia dapat meningkatkan pembelajaran IPA siswa kelas V SD. Kata Kunci: TGT, Multimedia, Pembelajaran IPA